2017
DOI: 10.3389/fphys.2017.00671
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heparin Receptor Transmembrane Protein 184a Regulates Angiogenesis in the Adult Zebrafish Caudal Fin

Abstract: Transmembrane protein 184A (TMEM184A) was recently identified as the heparin receptor in vascular cells. Heparin binds specifically to TMEM184A and induces anti-proliferative signaling in vitro. Though it is highly conserved, the physiological function of TMEM184A remains unknown. The objective of this study was to investigate the expression and effects on vascular regeneration of TMEM184A using the adult zebrafish regenerating caudal fin as an in vivo model. Here, we show that Tmem184a is expressed in vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…TMEM184A (also called Sdmg1) localizes to endosomes in mouse Sertoli cells and is required for the normal localization of the plasma membrane SNARE protein Stx2 ( Best et al, 2008 ). TMEM184A also acts as a heparin receptor in vascular cells and regulates angiogenesis ( Farwell et al, 2017 ; Pugh et al, 2016 ). TMEM184B localizes to recycling endosomes in mouse neurons and is important for the maintenance of synaptic architecture ( Bhattacharya et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…TMEM184A (also called Sdmg1) localizes to endosomes in mouse Sertoli cells and is required for the normal localization of the plasma membrane SNARE protein Stx2 ( Best et al, 2008 ). TMEM184A also acts as a heparin receptor in vascular cells and regulates angiogenesis ( Farwell et al, 2017 ; Pugh et al, 2016 ). TMEM184B localizes to recycling endosomes in mouse neurons and is important for the maintenance of synaptic architecture ( Bhattacharya et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smc3 knockdown validation was confirmed by preparing MO1, MO2 and Std-MO injected fin lysates as described in Farwell et al (2017) . For evaluating the protein expression, western blotting technique using fluorescent secondary antibody was used as previously described ( Farwell and Lowe-Krentz, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to Cawley (2011), risk factors for obesity and the cardiovascular system are extremely widespread among urban adults in particular, which requires urgent policies to prevent the growth of chronic illness. Farwell et al (2017) demonstrated that the incidence of cardiovascular disease and its risk factors are two to three times higher in the urban area compared to rural study subjects. The study also shows that among industry employees, 27% of them were overweight and 41% face obesity.…”
Section: Determinants Of Health Policiesmentioning
confidence: 96%